Analysis of Pavement Dimension at Hang Nadim International Airport in Batam City, Indonesia - Fiqri Fansyuri Saragih; Ari Sandhyavitri; Hendra Taufik (JURNAL SAINTIS, 2020)
[EN] It was acknowledged that, the Hang Nadim International Airport’s aircraft movements increased significantly at recent 10 years period. The shift in aircraft dimensions and weights have raised questions whether or not the existing apron pavement dimensions are sufficient for accommodating the increase aircraft parking demands and to bear aircraft load changes. The purpose of this research is to evaluate and analyze the apron dimensions and pavement thickness at Hang Nadim Airport. This research was used two relevant methods as guidelines for calculating this apron dimension and thickness; ICAO (International Civil Aviation Organization) Anex 14 2013 and FAA (Federal Aviation Administration) 150/5320-6d. It was calculated that the apron dimension need to be expanded to 1600 m x 150 m for accommodating 31 aircraft parking in 2025 (11 units B747- 300 + 16 units B737-900 + 4 units F27). The apron thickness would be 46.2 cm of base course and 10 cm of subbase course.